荀子批判公孙龙“白马非马”的正当性 ：再探荀子与公孙龙“实”的概念 = The legitimacy of Xunzi’s criticism on Gongsun Long’s idea of “White horse is not a horse” : a revised study on Shi in Xunzi and Gongsun Long - 赖珉利 Lai, Min Lee (2017)
荀子与公孙龙是先秦名实思想的重要代表人物,其名实思想备受今哲的关注，但是对于两者“实”的研究今哲却有所局限，因而对于荀子批判公孙龙“白马非马”这么重要的命题都不受瞩目，甚至片面理解他们分歧的原因，因此，笔者重新以“实”的角度出发来探讨这个命题。而在两者“实”的探讨中，不难发现两者“实”其实具有一个共同的基础，但是在这个基础上，荀子与公孙龙的侧重点却有所不同。公孙龙的“实”特别注重与名的绝对对应关系，而荀子的“实”则较多元且具有能动性，这是因为荀子的“实”还被放入更大的脉络中去考量，而且这些考量因素背后还有一个最终的命名标准。因此，整合荀子的名实观可以发现，虽然其与公孙龙背后都具有一个共同的思维框架基础，但是荀子的名实思想却具有较广阔的视野，因此使之与公孙龙的名实思想呈现出分歧的现象，由此可知，荀子批判公孙龙“白马非马”的命题是经过了多层次、多深层的思考，所以其批判是具有正当性的。并且，通过本论文对两者“实”共通基础的发现，还希望可以提供学术界对先秦名实思想一个新的研究方向。Xunzi and Gongsun Long are important representatives for the relationshipbetween name and reality during Pre-Qin thoughts, and there has been much attention paidto them. However, there are some limitations in the study of “shi”, where Xunzi’s criticismof the “white horse is not a horse”. Such an important proposition is not subjected toattention, and resulting in a one-sided understanding for their differences. Therefore, the“shi” of Xunzi and Gongsun Long will be rediscussed in this thesis. In the "shi" discussion,it is not difficult to find that the "shi" has a common basis between Xunzi and Gongsun Long. Nevertheless, on this basis, their emphasis is different. Gongsun Long's "shi" special emphasis lies in the absolute relationship with the name, while Xunzi's "shi" is more diverse and dynamic. This is because Xunzi's "shi" has been put into a larger context for consideration, and there is a standard naming behind these considerations. Therefore, the integration for the name and reality thoughts of Xunzi can be found that it has a broader view although behind Xunzi and Gongsun Long’s view of the name and reality has a common thinking framework, so that the name and reality thoughts between Xunzi and Gongsun Long are different. This is a critique of legitimacy on Xunzi's criticism of Gongsun Long's "white horse is not a horse" proposition because it has a multi-level and deep thinking. Also, we hope our fundamental finding of "shi" between Xunzi and Gongsun Long can provide the academic circles to a new research direction for the name and reality of Pre-Qin thoughts.